STUDI KANDUNGAN KITOSAN CANGKANG KAPAH (Meretrix sp.) DI PANTAI AMAL LAMA - Prayogo, Edy; Rachmawani, Dori (Jurnal Harpodon Borneo, 2011)
Chitosan is a polysaccharide that obtained by deacetylation of chitin. In this present day, chitosan been widely applicated and exploited in many sector of human life. Oriental hard clam was which one of fisheries commodity of Tarakan city, however it shells not yet been optimally exploited. The purpose of this research was to know the content of chitosan in oriental hard clam shell at Amal Lama beach. Sample determined by purposive sampling method. Meanwhile the isolation chitosan are using Hong and Knorr methods. The data that collected is chitosan content (mg) in each of ten shells, analyzed by linear regression test. Based on result of the research,  known that chitosan content on each shells of oriental hard clam was -4,594 grams and every 1 cm wide addition of shell would increased the chitosan that consist on it amount to 1,329 grams. Furthermore, the result of regression linear test showed that size of Kapah shell affecting chitosan content in it, with contribution of 85,9% and  the remain 14,1% are influenced by other factors.Keywords : Oriental hardclam, chitosan content, Amal Lama beach